Fake News Explosion in Portugal and Brazil the Pandemic and Journalists’ Testimonies on Disinformation - Canavilhas, João (2022)
Orchestrated manipulations spread lies and can create an environment of uncertainty in society, leading to concerns from politicians, scholars, educators, and journalists, among others. In this paper we explore what the emergence of fake news (understood as false news) represents for journalists, trying to answer the following question: Does false news pose a threat to the credibility of good journalism, causing a disruption of the traditional work? To answer it, we interviewed a sample of journalists from various media organizations in Portugal and Brazil. Among the main findings, journalists are aware that fake news is a problem to be faced, as the blame for the dissemination of false news erroneously lies with the profession. They are conscious that something must be done and agree that the best way to fight against fake news is to invest in media literacy. Most of the journalists of our sample think they must be also more cautious to check sources for veracity and for political motivations. The results show that there is a resolve to reinforce the role of journalism in society